Characterization of child abuse in educational institutions in the town of Huancavelica 2013 - Gonzales, Paco Edwin (2020)
OBJECTIVE: To characterize child abuse in girls/children in educational institutions of the town of Huancavelica. METHODS: observational, descriptive level, inductive and deductive methods, simple descriptive design, population 847, sample census.RESULTS: 76.5% children (as) living in nuclear families and 23.5% in dysfunctional families, physical abuse mild 0.8% between 10 and 11 years, 1.3% boys and 0.8% girls; Mom mainly aggressor; moderate 6.6% over 10 years and 6.5% in 11 years; 9.7% 7.7% girls and boys, brothers aggressors, dad, cousin, uncle, neighbor, grandmother; severe 30.9% in 11 years and 30.1% over10 years, 43.1% girls and 37.4% boys, bullies mother, cousin, neighbor, brother, sister, young, stepfather and father. Being forms interchangeably in children / girls punching, slapping, kicking, pinching, pushing, pulling hair, whips, pulling of ears and belting; shoving, whipping. Psychological abuse moderate 3.4% male / female 10 years, 3.1% in 11 years, attackers mom, uncle and grandfather (a); severe 35.2% in male / female 11 years, 34.1% in 10 years; 49.7% girls and 41.8% boys, bullies mother, uncle, cousin, brother (s), partner (s), neighbor, father, brother, young and stepfather. Being the ways boys / girls would say it’s bad (a), threats of abandonment, tell him not to (a) want, you’re useless, you’re ugly (a), you are bad, your brothers are better than your, teasing, everything you do is wrong, threats of punishment, denial of permits, calls attention to cries, nicknames, insults, shouting, you’re a nuisance, they say they do not want. Moderate sexual abuse in children / girls in 10 years 6.6% and 6.0% in 11 years; 7.0% (59 cases) children and 9.0% (76 cases) girls; exercised unknown 4.1%, 3.4% uncle, brother-mate 1.7%, 1.3% Daddy-cousin, neighbor 1.2%, 0.4% stepfather, 0.2% and 0.1% young grandfather forms 41.6% being forced to touch the body another person, 20.0% asked him to touch his genitals, 11.3% gave him kisses that have produced discomfort; scene by 6.1% house of the girl, street 5.1%, 0.9% child home, sanitation 0.7%, 0.5% neighbor’s house, 0.4% house cousin, uncle house, neighboring house, house 0.2% abandoned, swimming pool, restaurant 0.1%, mild 2.0% and 1.5% at 10 and 11 years; 1.8% (15casos) children and 2.6% (22 cases) girls; exercised unknown 1.8%, 0.9% uncle, brother 0.5%, 0.4% cousin, grandfather-father 0.2%, 0.1% brother-young; 10.2% take away her clothes and bare observed (a), 6.4% do look at their genitals, 3.2% their clothes off in front of the child (a); by place of occurrence 1.5% house girl-street school 0.4%, 0.2% of children-pool house and 0.1% abandoned house house- cousin-uncle-house sanitary services; severe 0.8% and 0.6% in 10 to 11 years; 0.9% boys and 0.6% girls; exercised by 0.4% unknown-dad, brother-cousin 0.2% and 0.1%-young stepfather; 7.0% have suffered sexual violation, (8 boys and 5 girls); scene 0.6% house of the girl, street 0.5%, 0.4% and 0.1% school abandoned house.CONCLUSIONS: The children suffered severe physical and psychological abuse, the mother was recognized as the main aggressor, sexual abuse was moderate, showing greater domestic abuse.